WELFARE PACKAGE AND JOB SATISFACTION AMONG TEACHERS - Ibrahim Agbeyinka (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2025)
The developed world has recognized the vital role that education plays in the development of nations; every country wants to produce high-quality education that fosters character and knowledge. The impact of welfare programs on teachers' job performance is widely recognized worldwide. This study was designed to investigate welfare package and job satisfaction among teachers in Orhionmwon Local Government Area of Edo State. As a result, the sample consisted of eight secondary schools, of which eighty (80) respondents were drawn from the population. A questionnaire was designed and administered to be able to carry out the investigation. Data was gathered and analyzed using chi-square analysis. Findings were made which led the researcher to conclude that teachers’ welfare package gave job satisfaction to teachers in Orhionmwon Local Government Area of Edo State. This study recommends that organization's welfare package should be expanded to provide job satisfaction for its members.